Creep Studies in Aluminium-2.25WT.% Magnesium. - Fagbulu, J. Babaniyi (Obafemi Awolowo University, 2014)
In this project, a study of creep mechanism in an Al-2.25wt% Mg alloy is conducted at temperatures between 573K and 623K and stresses (α ) ranging from 7.70 to 48.10 Mpa. Using the dislocation network model, the characteristics features of recovery-controlled and glide-controlled creep mechanisms are delineated. One of the manifestations of the fundamental differences between these two mechanisms, it is demonstrated, is the disparity which should be observed between the experimentally observed obstacle strength parameter α exp in the equation